1. Doprowadź do najprostszej postaci .

c) . (x-4)+6(3x-2)-5(2-x)

d) . -(4-y)+7 (y-7)-(-3)(2y-6)


2 . Oblicz wartośc wyrażenia .

a) . -12-(4y[do potęgi drugiej]-7)+5x . <--- Dla x= -2 a dla y= 1/4

b) . 1/2a+2(-3b+a)-6 <-- dla a= 1 a dla b= 0,5


Z góry DZIĘKUJE .! ; * ;3

3

Odpowiedzi

  • prhz
  • Rozwiązujący
2009-12-12T21:59:02+01:00
1.
c) . (x-4)+6(3x-2)-5(2-x) = x-4 +18x-12-10-5x= 14x-26
d) . -(4-y)+7 (y-7)-(-3)(2y-6) = -4+y+7y-49+36y-18= 44y-71

2.
a) -12-(4y^-7)+5x = -12-(4(1/4)^-7)+5*(-2)= --12+1/2+7-10= -6+7-10=-9
b)1/2a+2(-3b+a)-6 = 1/2*1+2(-3*(0.5)+1)-6= 1/2+2(-1.5+1)-6=
= 1/2+1-6 = -4.5

^ potęga
Najlepsza Odpowiedź!
2009-12-12T22:05:06+01:00
C) . (x-4)+6(3x-2)-5(2-x)=x-4+18x-12-10+5x=24x-26
24x=26 /24
x=13/12

d) . -(4-y)+7 (y-7)-(-3)(2y-6)=-4+y+7y-49+6y-18=14y-71
14y=71 /14
y=5 i 1/70

a) . -12-(4y²-7)+5x . <--- Dla x= -2 a dla y= 1/4

=-12-4y²+7+5x=-4*1/16+5*(-2)-5=-1/4-15=-15 i 1/4

b) . 1/2a+2(-3b+a)-6 <-- dla a= 1 a dla b= 0,5

1/2a-6b+2a-6=2,5a-6b-6=2,5-3-6=-6,5

2009-12-12T22:08:00+01:00
1.
c) (x-4)+6(3x-2)-5(2-x)=
x-4+18x-12-10+5x= 24x -26

d) -(4-y)+7 (y-7)-(-3)(2y-6)=
-4+y +7y-49+6y-18=14y-71

2.
a) -12-(4y[do potęgi drugiej]-7)+5x . <--- Dla x= -2 a dla y= 1/4
-12+4y²+7+5x = -12+4 *(¼)² + 7 +5 *(-2)=
-12+½+7-10= -6+7-10=-9

b) 1/2a+2(-3b+a)-6 <-- dla a= 1 a dla b= 0,5
½ a - 6b+12-6= 0,5 * 1-6 * 0,5 +12-6= 0,5-3+12-6=3,5